Fun POAC, A Learning Media for Human Resources Course - Imam Bukhori; Elfia Nora; Sopiah Sopiah (Universitas Negeri Malang, 2021)
This type, of course, consists of compulsory courses, prerequisites, concentrations, and electives. Human Resource Management courses are compulsory courses that must be followed by all undergraduate students of the Department of Management at the Faculty of Economics, Malang State University. The development of Fun POAC Human Resources Application as an e-learning medium in this human resource management course is to create and develop electronic learning media which will be able to make it easier for students to understand how planning, organizing, moving, and controlling human resources in an organization, Making learning in resource management courses is not boring and interesting because it is not only encouraged in listening to what lecturers say but is packed with application devices with various accessories and interesting features that can make students motivated to open, read and understand learning materials, assignments and practices. The material on the application is packaged for one semester lectures. The e-learning media developed consists of fun planning HR, Fun Organizing HR, Fun Actuating HR, and fun controlling desktop-based menus so that students or those who want to use this application can install it on their respective computers or laptops. The development method carried out is the Borg &Gall development model (2005) using waterfall grooves(waterfall)at the stage of development. The development stages start from needs analysis, product planning, product development, trial/implementation (validation), revision, and report creation. The product results in the form of the